2019
DOI: 10.3389/fmicb.2019.00300
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Enterococcus Isolated From Artisanal Dairy Products

Abstract: The present study focused on probiotic characterization and safety evaluation of Enterococcus isolates from different artisanal dairy products. All the isolates exhibited inhibitory activity against several food spoilage bacteria and food-borne pathogens, including Shigella flexneri, Staphylococcus aureus, Listeria monocytogenes, Yersinia enterocolitica, Klebsiella pneumoniae, Escherichia coli , and Bacillus subtilis . The PCR results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 67 publications
(82 reference statements)
7
88
0
Order By: Relevance
“…The survivability of these isolates in bile salt was measured according to Nami et al (26). Briefly, the MRS medium was prepared with 0.3% and without bile salt.…”
Section: Acid and Bile Salt Resistance Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The survivability of these isolates in bile salt was measured according to Nami et al (26). Briefly, the MRS medium was prepared with 0.3% and without bile salt.…”
Section: Acid and Bile Salt Resistance Assaysmentioning
confidence: 99%
“…Since Enterococcus emerge as the major opportunistic pathogen of humans and animals, the occurrence of virulence determinants was detected. The absence/presence of virulence factor genes for the isolated strains M2-3, M5-8, and M6-29 was performed using PCR amplification with primers and conditions reported previously (26,31). The primers and reaction conditions of PCR for the virulence factors were listed in Table 1 (32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Detection Of Potential Virulence Factorsmentioning
confidence: 99%
“…The use of Enterococcus species may be a controversial issue; however, certain Enterococcus species can be used as probiotic, starter and protective cultures, even as food and feed supplements (Giraffa 2003;Franz et al 2011;Mullan 2014). Nami et al (2019) suggested that Enterococcus isolates might be excellent candidates for the production of functional foods to promote health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect effects include production of lactic acid which decreases the pH, production of H 2 O 2 that interacts with the toxins produced by pathogens, synthesis of bacteriocins and mucins (Hu et al, 2017;Islam et al, 2016;Dinkçi et al, 2006). Upon ingestion, probiotics exert some beneficiary effects on human body, such as (i) reducing the duration of infectious and/or antibiotic associated diarrhea through influencing enteric nervous system and/or immune system to produce neuropeptides, cytokines or hormones that minimize secretion of water and electrolytes across the intestinal epithelium (Rahman et al, 2018;Andersson et al, 2001), (ii) control of lactose intolerance through delivery of microbial lactase to small intestine (Sanders, 2003), (iii) control of irritable bowel syndrome through alteration of population of intestinal microflora (Rahman et al, 2018;Sanders et al,2003), (iv) prevention of ulcers associated with Helicobacter pylori infection through antipathogen activity (Sanders, 2003;Nami et al, 2019), (v) prevention of urinary tract infection, kidney stones and flair-ups of Chron"s disease (Reid, 2005), (vi) prevention of inflammatory bowel disease through down regulation of inflammatory response (Sanders, 2003), (vii) exhibition of anti-mutagenic and anti-carcinogenic features through mutagen absorption and inhibition of carcinogen producing microflora (Sanders, 2003;Nami, 2019), (viii) increased intestinal mucosal barrier (Ahl et al, 2016). Lactic acid bacteria (LAB) are a major broad group of probiotic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are a major broad group of probiotic bacteria. LAB are gram positive, non-sporing, catalase negative, cocci-shaped, usually non-motile organisms that are devoid of cytochrome C and are nonaerobic, but are aerotolerant and acid tolerant which produce lactic acid as the major end product (Agrawal, 2005;Nami et al, 2019;Chowdhury et al, 2012). These microbes are ubiquitous in nature and are indigenous inhabitants of the human gastrointestinal tract, vagina and human skin, but are also found in soil, water, vegetables products, meats, fermented and cooked meat and dairy products (Andersson et al, 2001;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%